A fluid mechanical model for two-phase flows - Blesgen, Thomas (Computer Assisted Methods in Engineering and Science, 2023)
A modified Allen- Cahn equation is combined with the compressible Navier- Stokes system. After a physically motivated modification of the stress tensor, for the resulting equations the second law of thermodynamics is valid. The model can be used to describe the forming of gas phases in a flowing liquid.